Building academic bridges: integration of countries for the teaching of parasitic zoonoses a one health framework - Hernández-Ruso, Zully María (2025)
The workshop “Parasitic Zoonoses in the Context and Approach of One Health” was held within the framework of the International Congress of Neotropical Parasitology in 2024, an event that brought together multiple specialized symposia dedicated to the region’s health challenges. The purpose of the workshop was to strengthen the comprehensive understanding of parasitic zoonoses from the “One Health” paradigm, which recognizes the interdependence among human, animal, and environmental health as a single, dynamic, and deeply interconnected system. This article aims to disseminate an integrative disciplinary experience developed by the academic community under the One Health approach to parasitic zoonoses. The participation of specialists from Peru, Mexico, Colombia, Uruguay, and Brazil enriched the regional perspective and enabled the discussion of parasitological issues from diverse socio-ecological contexts of the Neotropics. The program was structured around five thematic axes: (1) conceptual foundations of the One Health approach; (2) parasitic zoonoses transmitted by companion animals and their relevance in urban environments; (3) parasitic zoonotic diseases of livestock importance; (4) parasitic ichthyozoonoses; and (5) parasites in aquaculture, where the main health challenges in production units were analyzed, along with transmission risks between farmed and wild environments, and the need to implement preventive strategies under the One Health framework to strengthen aquaculture sustainability. This last axis was reinforced through a specialized workshop led by Brazilian experts, providing updated knowledge on applied parasitology in Neotropical aquaculture systems. The development of the workshop was integrated with academic spaces of the congress, such as the II One Health Symposium, the V Neotropical Ichthyoparasitology Symposium, the II Leishmaniasis Symposium, the II Neotropical Chagas Disease Symposium, and the I Neotropical Plant Health Symposium, which allowed for deep interdisciplinary exchange by integrating perspectives from human, veterinary, environmental, agricultural, fisheries, and aquaculture parasitology. The outcomes of this academic experience highlight the urgency of strengthening local and regional capacities, promoting international collaboration, and consolidating coordinated strategies for surveillance, prevention, and control of parasitic zoonoses, particularly those associated with expanding productive systems such as aquaculture. Overall, the workshop reaffirms the value of the One Health approach as an essential tool for addressing emerging and persistent challenges that impact human, animal, and environmental health in the Neotropical region.